The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ajhg.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death Due to Deficiency of the Mitochondrial Inorganic Pyrophosphatase PPA2

Abstract: We have used whole-exome sequencing in ten individuals from four unrelated pedigrees to identify biallelic missense mutations in the nuclear-encoded mitochondrial inorganic pyrophosphatase (PPA2) that are associated with mitochondrial disease. These individuals show a range of severity, indicating that PPA2 mutations may cause a spectrum of mitochondrial disease phenotypes. Severe symptoms include seizures, lactic acidosis, cardiac arrhythmia, and death within days of birth. In the index family, presentation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 20 publications
2
72
0
1
Order By: Relevance
“… “OCR”, oxygen consumption rate. References: “G16” (Guimier et al, ); “K16” (Kennedy et al, ); “V18” (Vasilescu et al, ). PPA2 : GenBank Reference Sequence NG_053007.1. …”
Section: Discussionmentioning
confidence: 99%
“… “OCR”, oxygen consumption rate. References: “G16” (Guimier et al, ); “K16” (Kennedy et al, ); “V18” (Vasilescu et al, ). PPA2 : GenBank Reference Sequence NG_053007.1. …”
Section: Discussionmentioning
confidence: 99%
“…Ppa2 hydrolyzes inorganic pyrophosphate (PPi) into two phosphates, which is an essential activity for diverse biosynthetic reactions and for cellular energy metabolism (Guimier et al, ). Knockdown of Ppa2 has been shown to result in growth defects and loss of mitochondrial DNA in S. cerevisiae (Lundin et al, ), while Ppa2‐deficient cells might have limited ATP synthesis (Kennedy et al, ). In this study, Ppa2 was found to be downregulated suggesting that the failure of energy metabolism may be a fundamental mechanism in ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac conduction defects have been reported frequently in children and adults with KSS, and complete heart block may be a life‐threatening event in these individuals, indicating a need for regular screening ECGs [81]. Sudden death is also a feature of PPA2 mutations, and implantation of a cardiac defibrillator may be life‐preserving in affected individuals [82]. Wolff–Parkinson–White has been reported in LHON, MELAS and Leigh syndrome caused by the m.13513G>A mutation [44,58,83].…”
Section: Other Phenotypes: a Systems Approach To Mitochondrial Diseasmentioning
confidence: 99%